O poder da interjeição na performance trágica - Menezes Neto, Nelson de Aguiar (2025)
In Frogs 1028, Dionysus states that he rejoyced when Aeschylus in the Persians lamented for the death of Darius, and the chorus straightway clapped their hands and said, "Ee-ow!" (εΐπεν 'ίανοϊ'). In doing so, Aristophanes highlights the interjection as a particular component of theatrical conventions. Embedded in a tradition where lógos corresponds to word in action, the use of this lexical structure in Greek tragedy thus appears as a fundamental element for the functioning of this poetic genre. It is a refined strategy of enunciation that serves the tragic purposes of producing emotional effects through oralized speech. Without a denotative or descriptive function, but with a rich variation of possible meanings, it is pure mimetic performance, marked by the spontaneous expression of ineffable feelings. In this paper, we propose a discussion of the mimetic character of the interjection in tragedy-its phonetic ability to imitate reality-by examining its use in Aeschylus's Persians, a work considered "a great lament." The goal is to understand the fundamentally sounding nature of the tragic discourse arrangement and highlight a unique Greek practice of using language and producing speech.